2004
DOI: 10.1016/j.trstmh.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and morbidity of Schistosoma mansoni infection in a fishing community along Lake Albert in Uganda

Abstract: Schistosoma mansoni infection, associated morbidity and symptoms were studied in Piida fishing community at Butiaba, along Lake Albert, Uganda, from November 1996 to January 1997. The study revealed that S. mansoni is highly endemic with an overall prevalence of 72%, a mean intensity of 419.4 eggs per gram (epg) faeces (geometric mean for positives only), with 37.8% of males and 33.0% of females excreting over 1000 epg. Prevalence and intensity peaked in the 10-14 year old age group and decreased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
73
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 20 publications
11
73
4
Order By: Relevance
“…Likewise, in the case of hepatomegaly, we were unable to distinguish clear associations, which may have been due to the fact that these observed morbidities were likely to have been multifactorial, with S. mansoni infection being only one of a number of potential causes. 57 There are often many factors (genetic and possibly most importantly malaria, which is transmitted throughout the year in Mali 58 ) other than S. mansoni that can cause liver enlargement, and their role and interaction with S. mansoni infection also requires further clarification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the case of hepatomegaly, we were unable to distinguish clear associations, which may have been due to the fact that these observed morbidities were likely to have been multifactorial, with S. mansoni infection being only one of a number of potential causes. 57 There are often many factors (genetic and possibly most importantly malaria, which is transmitted throughout the year in Mali 58 ) other than S. mansoni that can cause liver enlargement, and their role and interaction with S. mansoni infection also requires further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ultrasonography is currently the diagnostic tool of choice for detecting pathologic conditions associated with schistosomiasis, such as dilatation of the renal pelvis, bladder wall lesions, liver fibrosis and enlargement, and dilatation of the portal vein. 8,9 For detection of infection with S. haematobium, ultrasonography is an established method for detecting urinary tract pathologic effects not only in the hospital setting, [10][11][12][13] but also in field-based studies, 14 with the advantage of being non-invasive, relatively simple to perform, well accepted by communities, and providing a direct image of the pathologic changes. 15 Additionally, ultrasonography provides sensitive and precise measurements of S. mansoni-associated pathologic changes 16,17 In the attempt to objectively define and categorize the pathologic changes associated with schistosomiasis and to standardize the different scoring systems used in the past in different disease-endemic areas, 18,19 successive ultra-sound consensus meetings were held in Niamey, Niger in 1996 and Belo Horizonte, Brazil in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in infection prevalence in male and female participants are mostly attributed to differences in exposure habits, which are usually occupation-based. 22 For instance, in our study communities, women have more contact hours with these Schistosomainfested water bodies carrying out domestic chores, such as washing, than men, because access to a clean water supply and good sanitation is limited in most households. However, findings from a recent study in Uganda 23 showed that men were more likely to be infected with S. mansoni than their female counterparts, because they have more water contact hours with infested water during their fishing activities.…”
Section: Discussionmentioning
confidence: 88%
“…Similar trends in the intensity of infection have been documented in other S. mansoni-endemic areas. 22,23 Differences in parasite distribution among the different age groups have been attributed to behavioral changes and acquisition of immunity to infection in the older age groups. 24,25 Although it is true that immunity to Schistosoma infection develops over time and in line with increasing age, the trend may not be so for behavioral change as a factor for infection reduction among adults living in S. mansoni-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that determine the level of morbidity in an exposed population include: the degree and length of exposure [4], intensity of infection, coinfection [5] and ability to modulate those reactions [4]. Low infection rates over prolonged periods of time characterize schistosome infections of people living in endemic areas.…”
Section: Introductionmentioning
confidence: 99%